2018
DOI: 10.1536/ihj.17-465
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptive Remodeling of the Anterior Mitral Leaflet and Chordae Tendineae Is Associated with Mitral Valve Function in Advanced Ischemic and Nonischemic Dilated Cardiomyopathy

Abstract: The degree or nature of functional mitral regurgitation (MR) is not necessarily correlated with the size or function of the left ventricle (LV). We hypothesized that the anatomical structure of the mitral valve (MV) complex might play a role in functional MR in ischemic or nonischemic dilated cardiomyopathy (DCM).The structure of the LV and MV complex in DCM patients (n = 29) was assessed using electrocardiogram-gated 320-slice computed tomography and was compared with that in healthy patients (n = 12). Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
(29 reference statements)
0
23
0
Order By: Relevance
“…The PL length difference was not significant (16.1 ± 2.6 vs. 15 ± 3.1 mm; p = .08). It is as well evident in many studies that the AL increases its length more than the PL 35,36 …”
Section: Biological Mechanisms Of MV Plasticitymentioning
confidence: 83%
See 1 more Smart Citation
“…The PL length difference was not significant (16.1 ± 2.6 vs. 15 ± 3.1 mm; p = .08). It is as well evident in many studies that the AL increases its length more than the PL 35,36 …”
Section: Biological Mechanisms Of MV Plasticitymentioning
confidence: 83%
“…It is as well evident in many studies that the AL increases its length more than the PL. 35,36 In patients who had AMI, and early revascularization in almost all cases, Beaudoin et al 37 demonstrated increased thickness of the MLs 2 years post AMI and a further increase thereafter. There was a progressive reduction of the AL excursion and patients who developed more than mild MR had thicker MLs than patients who did not.…”
Section: Trigger Related To Myocardial Infarctionmentioning
confidence: 99%
“…Leaflet area, however, failed to increase in proportion to the geometric demands imposed by PM displacement in patients with IMR, in contrast to those with LV remodeling and no IMR. Yoshida et al 17 found that patients with dilated cardiomyopathy and no or low IMR had larger and longer AL if compared with normal hearts. PL was neither larger nor longer than normal, supporting the theory that the mechanical stretching produced by the posteriorly located PM in the dilated heart is more potent in the AL than in the PL.…”
Section: Discussionmentioning
confidence: 99%
“…The PL is positioned vertically. 3D, three-dimensional; AL, anterior leaflet; IMR, ischemic mitral regurgitation; PL, posterior leaflet Other techniques have been proposed in association with RMA.Among these, relocation of the posteromedial PM34 or PM approximation35 are aimed to improve the outcome of patients who undergo surgery for IMR addressing directly the initial cause of IMR.However, the study from Yoshida et al17 clearly shows that severely dilated hearts with ischemic or idiopathic cardiomyopathy, with high diameters (median 68 mm) and volumes, could have no or mild IMR if the mitral leaflets and chordae tendinae remodel correctly. Moderate or severe IMR occurs only if this process is incomplete.…”
mentioning
confidence: 99%
“…Rupture of mitral chordae tendineae is one of the causes of acute mitral valve regurgitation, which can lead to acute pulmonary edema and cardiogenic shock [12]. It is one of the most common valvular heart diseases, which is secondary to Marfan syndrome, connective tissue disease, coronary heart disease, congenital heart disease, infective endocarditis, rheumatic heart disease and degenerative valvular disease [13]. It often occurs because of the weakness of mitral chordae tendineae, papillary muscles, and abnormal valve position or shape.…”
Section: Discussionmentioning
confidence: 99%